Preterm birth, low fetal growth and risk of suicide in adulthood: a national cohort and co-sibling study. (10th March 2021) - Crump, Casey; Sundquist, Jan; Kendler, Kenneth S; Edwards, Alexis C; Sundquist, Kristina
Abstract: Background: Adverse perinatal exposures have been associated with psychiatric disorders and suicidal behaviours later in life. However, the independent associations of gestational age at birth or fetal growth with suicide death, potential sex-specific differences, and causality of these associations are unclear. Methods: A national cohort study was conducted of all 2 440 518 singletons born in Sweden during 1973–98 who survived to age 18 years, who were followed up through 2016. Cox regression was used to compute hazard ratios (HRs) for suicide death associated with gestational age at birth or fetal growth while mutually adjusting for these factors, sociodemographic characteristics and family history of suicide. Co-sibling analyses assessed the influence of unmeasured shared familial (genetic and/or environmental) factors. Results: In 31.2 million person-years of follow-up, 4470 (0.2%) deaths by suicide were identified. Early preterm birth (22–33 weeks) was associated with an increased risk of suicide among females [adjusted hazard ratio (HR), 1.97; 95% confidence interval CI), 1.29, 3.01; P = 0.002) but not males (0.90; 0.64, 1.28; P = 0.56), compared with full-term birth (39–41 weeks). Small for gestational age was associated with a modestly increased risk of suicide among females (adjusted HR, 1.27; 95% CI, 1.08, 1.51; P = 0.005) and males (1.14; 1.03, 1.27; P = 0.02). However, these associations were attenuated and non-significant after controlling for shared familial factors. Conclusions: In this large national cohort, preterm birth in females and low fetal growth in males and females were associated with increased risks of suicide death in adulthood. However, these associations appeared to be non-causal and related to shared genetic or prenatal environmental factors within families.